Thomas Reid and the story of epistemology - Wolterstorff, Nicholas (Cambridge University, 2013)
This important book will do much to reestablish the significance of Thomas Reid for philosophy today. Nicholas Wolterstorff has produced the first systematic account of Reid's epistemology. Relating Reid's philosophy to present-day epistemological discussions the author demonstrates how they are at once remarkably timely, relevant, and provocative.